Small Heterocyclic D-π-D-π-A Push-Pull Molecules with Complex Electron Donors - Kulhánek, Jiří; Pytela, Oldřich; Bureš, Filip; Klikar, Milan (Wiley-VCH, 2021)
A large series of small push-pull chromophores based on electron-withdrawing N,N'-dibutylthiobarbituric acid has been designed and successfully synthesized. The electron donating part involves common mesomeric donors such as methoxy, N,N-dimethylamino, N,N-diphenylamino, and piperidin-1-yl groups. Five-membered heteroaromatics, namely thiophene, N-methylpyrrole, and furan have been employed as electron rich pi-linkers and auxiliary donors. Structural analogues bearing aromatic 1,4-phenylene linker were also synthesized for comparison. Fundamental thermal and optoelectronic properties were studied by differential scanning calorimetry, cyclic voltammetry, and absorption spectroscopy. Thorough structure-property relationships were elucidated, focusing mostly on type of the used pi-linker and donor. All experimental conclusions are corroborated by theoretical calculations. The study has shown that a complex donor moiety may be built by properly combining mesomeric and auxiliary donors. Whereas strong mesomeric donor (amino) suppresses the donating effect of auxiliary donors/pi-linkers, a combination of weak donor (methoxy) appended at a five-membered heterocycle pronounces the donating ability of the latter.
Malé heterocyklické D-π-D-π-A push-pull Molekuly s komplexními elektron donory
Keywords: DFT calculations; heteroaromatic donors; N; N'-dibutyl-2-thiobarbituric acid; optoelectronic properties; small push-pull chromophores; DFT kalkulace; heteroaromatické donory; N'-dibutyl-2-thiobarbiturová kyselina; optoelectronické vlastnosti; push-pull chromofory